Peran Aviation Security dalam Pengawasan dan Penanganan Dangerous Goods dan Prohibited Item di Bandar Udara Tjilik Riwut Palangka Raya - Mia Anjelintina; Kifni Yudianto (Pusat Riset dan Inovasi Nasional, 2024)
Tjilik Riwut Palangka Raya Airport is the largest airpot in Central Kalimantan Privince. This airport has a runway size of 2,500 x 45cm. this airport is managed by PT.Angkasa Pura II. Aviation Security (AVSEC) based on the regulation of the Director General of Air Transportation with Number: SKEP 2756/XII/2010 concerning procedures for checking the security of passengers,aircraft officers,and luggage transported by aircraft and individuals. Thes purpose of this study is to determine the differences between Security Check Point1 and Security Check Point 2 and to determine the work system of supervision and handling of Dangerous Goods and Prohibited Item at Tjilik Riwut Palngka Raya Airport. This research is a qualitative research with data collection techniques,namely observasion,documentation,and interview. Data analysis techniques used are data collection,data reduction,data presentasion, and drawing conclusions. The results of the research conducted by the researcher showed that there was nosignificant difference between Security Check Point 1 and Security Check Point 2 and the work system of Aviation Security officers was in accordance with existing procedures in the supervision and handling of Dangerous Goods and Prohibited Item.